Improving Water Solubility and Skin Penetration of Ursolic Acid through a Nanofiber Process to Achieve Better In Vitro Anti-Breast Cancer Activity - Hsuan Fu; Tzu-Hui Wu; Chih-Peng Ma; Feng-Lin Yen (MDPI AG, 2024)
Woman's breast cancer has always been among the top ten causes of cancer death, and nearly 2% to 5% of locally advanced breast cancers develop a fungating breast wound. Fungal breast cancer leads to skin ulcers, wound ruptures, and other bacterial infections in patients. Ursolic acid (UA), a natural pentacyclic triterpene compound, is widely distributed in many fruits. Previous studies demonstrated that UA has anti-breast cancer, antifungal, and improved wound-healing effects. UA, however, had poor water solubility and low bioavailability, restricting its clinical application. Nanofibers have the advantages of rapid dissolution, improved stability, and bioavailability of active ingredients. We had successfully prepared ursolic acid nanofibers (UANFs) and effectively improved their water solubility and skin penetration. UANFs can increase water solubility by improving the physicochemical properties, including increased surface area, intermolecular bonding with excipients, and amorphous transformation. Furthermore, UANFs had better anti-breast cancer activity than raw UA. UANFs inhibited the expression of phospho-signal transducer and activator of transcription 3 (STAT3) and phospho-extracellular regulated protein kinases (ERK)1/2, and induced cleaved caspase-3 protein expression, but had no effect on the raw UA treatment. In summary, UANFs enhanced the skin absorption of UA and improved its anti-breast cancer efficacy. We expect that UANFs can be used as an anti-breast cancer treatment and reduce the discomfort of breast cancer patients during dressing changes, but more detailed efficacy and safety trials still need to be conducted in further studies.